Peran Keluarga dan Peningkatan Pendidikan Anak Perempuan Terhadap Gender di Kecamatan Kepil Kabupaten Wonosobo - Sri Maryati; Muhamad Hani Yusuf; Umi Sifatul Rofiah; Hartini; Zainuddin Prayitno Widodo (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The family plays a fundamental role in the education of girls in Warangan Village, Kepil District, Wonosobo Regency, encompassing various essential dimensions, including physical and health education, emotional education, intellectual development, moral education, socio-religious education, and spiritual (faith-based) education. These roles are not only implemented through verbal instruction, but also through consistent modeling, habituation, and continuous guidance in daily life, positioning the family as the primary and most influential educational institution for girls. In addition, families also contribute to strengthening gender-responsive education by encouraging girls to pursue higher education, internalizing religious values from an early age, fostering religious practices, instilling moral values, and developing mental resilience, social competence, and intellectual capacity, all of which contribute to shaping independent and competitive individuals. Furthermore, the study identifies a transformation in gender awareness within the community, reflected in increasing family support for girls’ higher education and a gradual shift from traditional patriarchal perspectives toward more equal gender relations, although challenges such as economic limitations and residual traditional mindsets that are not fully gender-responsive still exist. Therefore, it can be concluded that the family is a key actor in promoting gender equality while simultaneously enhancing the educational quality and social mobility of girls in rural communities.